2000
DOI: 10.1177/154193120004402702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Warning Symbol Explicitness and Warning Color on Behavioral Compliance

Abstract: Previous research has shown that signal words, warning colors, and symbol explicitness can affect waming effectiveness and hazard perceptions. This study assessed the impact of two warning colors, two warning sign types, and two levels of symbol explicitness on college student behavior. Scaffolding was erected in front of a building to simulate a construction area, and warning signs were placed on one door instructing individuals to use an alternate exit. Warning effectiveness was assessed by comparing transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…Participants scored almost the same regardless of the design, which could indicate that additional changes to the label of OTC acetaminophen would not surely improve compliance. Interestingly, our results are consistent with previous findings that demonstrate warnings could have little effect on consumers' behavior, since there are non-warning factors that can impact the warning process (Frantz et al, 2005;E. F. Shaver & Braun, 2000;Eric F Shaver et al, 2006).…”
Section: Why Label Warnings Have Little Effectiveness?supporting
confidence: 92%
See 1 more Smart Citation
“…Participants scored almost the same regardless of the design, which could indicate that additional changes to the label of OTC acetaminophen would not surely improve compliance. Interestingly, our results are consistent with previous findings that demonstrate warnings could have little effect on consumers' behavior, since there are non-warning factors that can impact the warning process (Frantz et al, 2005;E. F. Shaver & Braun, 2000;Eric F Shaver et al, 2006).…”
Section: Why Label Warnings Have Little Effectiveness?supporting
confidence: 92%
“…F. Shaver & Braun, 2000;Eric F Shaver et al, 2006). For instance, a study conducted by Shaver et al (2000) to evaluate the effect of different warnings on behavioral compliance, found that while there was an effect as consequence of the presence of a warning sign, changes to the design of the warning (e.g. : color, sign type, or symbol explicitness) had no effect on behavioral compliance.…”
Section: Why Label Warnings Have Little Effectiveness?mentioning
confidence: 99%
“…Actual compliance rates (from Frantz et al, 1993;Frantz et al, 2000; using the lax criterion from both studies) showed that compliance for the ANSI-style label (M = 16.7%) was a. Shaver and Braun (2000) reported that actual behavior was significantly affected by presence of any sign (compared to no sign) and that no difference was found between the three sign conditions.…”
Section: Scenario 2: File Cabinet Labelsmentioning
confidence: 96%
“…For each label, participants were asked how many people out of 100 would notice the labels on the filing cabinet and also how many people out of 100 would follow the warning's target statement to load the bottom drawer first. Shaver and Braun (2000) studied the behavior of people using a set of three doors to a campus building. Specifically, signs were posted on both sides of the left-most of three door-ways that told people to use the center exit of the building due to the fact that overhead construction was being performed outside the building.…”
Section: Scenario 2: File Cabinet Labelsmentioning
confidence: 99%
See 1 more Smart Citation